Affective temporalities in Gob Squad’s Kitchen (you’ve never had it so good) - Pais, Ana (2014)
In this article I will be drawing upon affect theory to unpack issues of authenticity, mediation, participation in the production Gob Squads’s Kitchen, by Gob Squad. English/German collective reconstructed Andy Warhol’s early film Kitchen, shot 47 years before, in the flamboyant Factory, starring ephemeral celebrities such as Eve Sedgwick. Alongside Eat (1964), Sleep (1963) and Screen Test (1964-66). Although it premièred in Berlin, in 2007, the show has been touring in several countries and, in 2012, it received the New York Drama Desk Award for Unique Theatrical Experience. I will be examining how the production’s spatial dispositive creates a mediated intimacy that generates affective temporalities and how their performativity allows us to think of the audience as actively engaged in an affective resonance with the stage. Intimacy creates worlds (BERLANT, 2000). It brings audience and performer closer not only to each other but also to the shifting moment of Performance Art’s capture by institutional discourses and market value. Unleashing affective temporalities allows the audience to embody its potency, to be, again, “at the beginning”. Drawing upon André Lepecki’s notion of reenactments as activations of creative possibilities, I will be suggesting that Gob Squads’s Kitchen merges past and present by disclosing accumulated affects, promises and deceptions attached to the thrilling period of the sixties in order to reperform a possibility of a new beginning at the heart of a nowthen time. In conclusion, this article will shed new light on the performative possibilities of affect to surmount theatrical separation and weave intensive attachments.